GENERATIVE AI-ENABLED COMPLIANCE DOCUMENTATION AND AUDIT TRAIL AUTOMATION FOR GLOBAL DATA CENTER GOVERNANCE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
Global data centers execute complex data processing activities, often across multiple jurisdictions, attracting a multitude of sector-specific compliance requirements. Faced with mounting pressure from regulators and civil society, organizations must demonstrate their ability to meet these demands. While most possess abundant technology assets, many struggle to maintain updated compliance documentation, such as privacy impact assessments and policies. Automating the generation of narrative compliance artifacts would assist teams in addressing customer requests and fulfilling reporting obligations to trusted partners. Additionally, an auditable trail of compliance-related activities, with identifiers to sources and supporting data, would help organizations respond to regulatory inquiries with less effort. Generative AI Technics are well-suited for these use cases.Generative AI enables the creation of a wide variety of content, including text, images, and sounds. Large language models, one of the main types of Generative AI, are trained on massive datasets to understand and generate humanlike text. Following proper usage guides and user feedback, these models can generate convincingly logical responses that address the user’s intent. However, they are prone to factual inaccuracies and do not understand the content they produce. Organizations seeking to leverage large language models must therefore establish guidelines and processes that control input quality, ensure consistency and correctness, and provide indications of trustworthiness and reliability.